Comprehensive Risk Assessment of Health-Related Hazardous Events in the Drinking Water Supply System from Source to Tap in Gaza Strip, Palestine. (29th January 2020) - Abuzerr, Samer; Hadi, Mahdi; Zinszer, Kate; Nasseri, Simin; Yunesian, Masud; Mahvi, Amir Hossein; Nabizadeh, Ramin; Hussien Mohammed, Shimels
Abstract : Background . The traditional approach in the management of the quality drinking water, and relying on end-product testing, has proven ineffective in protecting public health. Therefore, the transition to a systematic approach in drinking water supply systems management from the source to the consumer tap was taken as a water safety plan (WSP). Objective . The study aims to investigate the health-related hazardous events in order to decide on the best risk-reduction strategies in the supply of drinking water in the Gaza strip. Methods . A semiquantitative matrix method for risk assessment was applied. Also, chlorine residual, electrical conductivity, and nitrate concentration further tested in 109 water wells, 109 small-scale water desalination plants, 197 tanker trucks, and 384 households distributed over five governorates of the Gaza strip. Results . The mean of the measured chlorine residual values was less than the recommended national and international limits (0.2–1 mg/liter). The mean of electrical conductivity at catchment points and household municipal water taps was 2165.1  μ S·cm −1 and 2000  μ S·cm −1, respectively. Furthermore, zero percent of water samples met the recommended criteria, indicating that the groundwater in the Gaza strip is nonpotable. Only 12.8% and 8.8% of water samples met the permissible levels at catchment areas and municipal water at household, respectively, indicating sever health impacts on the public. Moreover, the most hazardous events were related to high levels of groundwater salinity, the low level of disinfection, the effect of electricity outages on the efficiency of the desalination process, and leakage of water from the tanker truck tank reservoirs. Therefore, urgent interventions are required to improve the quality of water and to mitigate the possible health effects. Conclusion . The prioritization of hazardous events that are proportional to the degree of their attributed risk could help guide in making the right risk-reduction decisions. Urgent interventions are required to improve the quality of water and to mitigate the possible health effects.